Pengembangan Modul Literasi Budaya Riau untuk Pembelajaran Keterampilan Menulis Teks Naratif Siswa Sekolah Dasar - Evi Rismawati; Eva Astuti Mulyani; Guslinda Guslinda (Lembaga Pengembangan Kinerja Dosen, 2025)
This study aims to develop a Riau cultural literacy module for elementary school students' narrative text writing skills that is valid, practical, and feasible to use. The method used in this study is Research and Development (R&D) with a 4D development model, which includes four stages: Define (needs analysis), Design (design), Development (development), and Disseminate (dissemination). The developed module was validated by three experts, namely teaching material experts, material experts, and language experts. Meanwhile, the practicality aspect was assessed through a practicality questionnaire given to teachers and students during a limited trial. Data collection techniques in this study include interviews, observations, and questionnaires. The data obtained were analyzed using quantitative analysis techniques and qualitative descriptions. The validation results showed that the developed teaching materials met the valid criteria with an average percentage of 96.1%. Meanwhile, the level of practicality of teaching materials based on the teacher's practicality questionnaire reached 83.3% with the category of